2017
DOI: 10.1007/s12012-017-9409-z
|View full text |Cite
|
Sign up to set email alerts
|

QT Prolongation as an Isolated Long-Term Cardiac Manifestation of Dichlorvos Organophosphate Poisoning in Rats

Abstract: Organophosphates (OP) are used extensively as pesticides and as chemical weapons. Cardiotoxicity is a major concern in survivors of the acute poisoning. To characterize the delayed cardiac effects of OP, rats were poisoned by intraperitoneal administration of dichlorvos. In group I, poisoning (0.25-, 0.75-, 1.4-LD) was followed by application of atropine and obidoxime. In group II, poisoning (0.35-, 0.5-LD) was done without antidotes. Cardiac evaluation included electrocardiography and echocardiography 2- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The hippocampus and amygdala are two brain regions that are known to be directly involved in spatial memory and emotional reactions, such as fear. Acute and chronic exposures to either chlorpyrifos (CPF) or dichlorvos (DDVP) have resulted in a wide range of toxicities, including cardiotoxicity, neurotoxicity, hepatotoxicity, renal toxicity, hematological toxicity, and immune system toxicity, among others [8,9,20,21,22,23]. Besides cholinesterase inhibition, these substances caused marked disruptions in normal oxidative functions [8,9,20,21,24].…”
Section: Introductionmentioning
confidence: 99%
“…The hippocampus and amygdala are two brain regions that are known to be directly involved in spatial memory and emotional reactions, such as fear. Acute and chronic exposures to either chlorpyrifos (CPF) or dichlorvos (DDVP) have resulted in a wide range of toxicities, including cardiotoxicity, neurotoxicity, hepatotoxicity, renal toxicity, hematological toxicity, and immune system toxicity, among others [8,9,20,21,22,23]. Besides cholinesterase inhibition, these substances caused marked disruptions in normal oxidative functions [8,9,20,21,24].…”
Section: Introductionmentioning
confidence: 99%
“…Mortality resulting from acute DDVP poisonings is associated with respiratory failure from inhibition of central (medullary) respiratory drive, unrestrained bronchial secretions, and bronchospasms as well as depolarizing barricade at the diaphragm and intercostals (neuromuscular junctions) [7,8]. Dichlorvos exhibits several harmful effects not limited to cardiotoxicity, hepatotoxicity, immune system toxicity, renal toxicity, and hematological toxicity [1,[8][9][10][11]. Studies have reported the neurotoxicity of DDVP in laboratory rats, but there is a paucity of information in respect to oxidative stress, neuroinflammation, apoptosis, lipid peroxidation, mitochondria dysfunction or aggregation of pathological proteins, that are regarded as the etiologies of neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%
“…CPF produced reactive oxygen species and oxidative stress that distressing normal cellular differentiation and development (3) and elevated malonadialdehyde (MDA) level that, considered as a marker of lipid peroxidation resulting from interaction of reactive oxygen species and cellular membrane that produced membrane damage by changing membrane characteristics (4) .CPF inhibits acethylcholinesterase activity that leads to over stimulation of cholinergic transmission mediated by nicotinic and muscarinic receptors, in tissues of the different organs. Chemicals including CPF are considered as a potential thyroid gland disrupter (5) Ginger (Zingiber officinale), has an effective protective role against oxidative stress and it is used as anti-emetic; it contains flavonoids and polyphenolic constituents that have antioxidant properties (6) .…”
Section: Introductionmentioning
confidence: 99%